A cross‐sectional investigation of cognition and epileptiform discharges in juvenile absence epilepsy. Issue 3 (2nd February 2023) - Dharan, Anita L.; Bowden, Stephen C.; Peterson, Andre; Lai, Alan; Seneviratne, Udaya; Dabscheck, Gabriel; Nurse, Ewan; Loughman, Amy; Parsons, Nicholas; D'Souza, Wendyl J.
Abstract: Objectives: Despite the prevalence of cognitive symptoms in the idiopathic generalized epilepsies (IGEs), cognitive dysfunction in juvenile absence epilepsy (JAE), a common yet understudied IGE subtype, remains poorly understood. This descriptive study provides a novel, comprehensive characterization of cognitive functioning in a JAE sample and examines the relationship between cognition and 24‐h epileptiform discharge load. Method: Forty‐four individuals diagnosed with JAE underwent cognitive assessment using Woodcock Johnson III Test of Cognitive Abilities with concurrent 24‐h ambulatory EEG monitoring. Generalized epileptiform discharges of any length, and prolonged generalized discharges ≥3 s were quantified across wakefulness and sleep. The relationship between standardized cognitive scores and epileptiform discharges was assessed through regression models. Results: Cognitive performances in overall intellectual ability, acquired comprehension‐knowledge, processing speed, long‐term memory storage and retrieval, and executive processes were 0.63–1.07 standard deviation (SD) units lower in the JAE group compared to the population reference mean, adjusted for educational attainment. Prolonged discharges (≥3 s) were recorded in 20 patients (47.6%) from 42 available electroencephalography (EEG) studies and were largely unreported. Duration and number of prolonged discharges were associated with reduced processing speed and long‐term memory storage and retrieval. Significance: Cognitive dysfunction is seen in patients with JAE across various cognitive abilities, including those representing more stable processes like general intellect. During 24‐h EEG, prolonged epileptiform discharges are common yet underreported in JAE despite treatment, and they show moderate effects on cognitive abilities. If epileptiform burden is a modifiable predictor of cognitive dysfunction, therapeutic interventions should consider quantitative 24‐h EEG with routine neuropsychological screening. The growing recognition of the spectrum of neuropsychological comorbidities of IGE highlights the value of multidisciplinary approaches to explore the causes and consequences of cognitive deficits in epilepsy.